Enforcement of murabahah, mudharabah, and qardhulhasan contracts in the syari'ah system - Setiawan Setiawan (Indonesian Journal of Islamic Economics Research, 2021)
This study examines the implementation of murabahah, mudharabah, and qardhulhasan contracts in the Syari'ah System at KSPPS Baitul Maal Wat-Tamwil "Article" of the Salatiga Religious Court. This study aims to determine the mechanism of murabahah contract in the circulation of funds, to find out the mechanism of circulation of mudharabah funds, and to find out the analysis of shari'ah compliance with the rotation mechanism funding. This type of research is this study using the type of descriptive research. The results showed the mechanism murabahah contract by using the borrower to choose the goods needed, then the cooperative buys the goods by notifying the borrower. The price and profit to be deposited to the cooperative, the mechanism for the circulation of mudharabah funds is that the distribution of profits or profits between investors and managers is carried out fairly between managers and investors, and analysis of shari'ah compliance (fulfillment of the concept of shari'ah) on the mechanism of circulation of funds can meet sharia principles as measured in implementing Islamic principles and laws.